332 Speech Dysfunction in Deep Brain Stimulation Patients. (1st April 2022) - Chandra, Vyshak; Wong, Joshua; Hegland, Karen; Herndon, Nicole; Foote, Kelly D.
Abstract : INTRODUCTION: Deep brain stimulation (DBS) is a neuromodulatory therapy that is predictably effective for treatment of Parkinson's disease (PD). The precise effect of DBS on speech function is variable, however, and patients with more impaired speech function prior to surgery are thought to be at increased risk of worsening speech function post surgically. METHODS: Patients with a diagnosis of Parkinson's disease who are at least 40 years old (at first DBS surgery) that have had speech assessments as part of normal clinical care 12 or fewer months prior to DBS surgery (pre-DBS) and within 12 months after surgery completion (post-DBS) were included in the study - 130 total patients. Preoperative and postoperative speech testing data was compiled, along with DBS programming settings including lead type (directional or conventional), pulse width, frequency, amplitude, active contacts, and battery type at time of speech evaluations (estimated to be 6- and 12-months post DBS surgery). RESULTS: A mixed effect linear model with lognormal errors to analyze the speech pathology severity scores. Site (STN, GPi), and hemisphere involvement (Unilateral, Bilateral) were modeled as completely crossed between-patient fixed effects. Speech severity, respiratory severity, and laryngeal severity were found to be significantly worsened post-operatively in patients that obtained GPi DBS, contrary to our original hypothesis. Orofacial severity worsened post-operatively in patients that obtained STN DBS. CONCLUSION: GPI DBS patients had several categories of statistically significant worsening of speech, contrary to our hypothesis. A future study based on target alone will not be useful, but preliminary data studying specific neuroanatomic localization of stimulation and activation of fibers should prove more fruitful.